Development of polyether block amide (PEBAX) nanocomposite membranes using nanoadsorbent from agricultural wastes as fillers for gas separation - Alia Aqilah, Ghazali (2020)
Over the past decade, membrane processes for gas separation are gaining a larger acceptance in the industry and the markets are competing with consolidated operations such as pressure swing absorption and cryogenic distillation. There have been intensive efforts in the development of better and more robust membrane material called nanocomposite membranes which involved the incorporation of nanoadsorbents such as zeolite and silica in the polymer matrix. Recently, interest has been given to nanoadsorbents derived from agricultural wastes due to their abundance, promising features, and reasonable adsorption performances compared to the conventional nanoadsorbents. Therefore, the purpose of this study is to develop, characterise, evaluate and optimise the nanocomposite membranes comprised of the coated polyether block amide (Pebax) filled with two different types of nanoadsorbent (pineapple peel and oil palm frond) on the commercial polyvinylidene fluoride (PVDF) support membrane. A 24 full factorial design (FFD) was utilized in this study to minimize the influenced factors during nanocomposite membrane preparation. A total of four factors were chose to run simultaneously and the responses were based on permeability (CO2, CH4, N2) and ideal selectivity (CO2/CH4, CO2/N2). For the preparation of flat sheet membrane, the factors include Pebax concentration (3 and 6 wt%), types of nanoadsorbent (pineapple peel and OPF), nanoadsorbent concentration (0.5 and 5 wt% based on Pebax weight) and sonication time (15 and 30 min). Two most influenced factors towards the final separation efficiency were further study for optimisation using central composite design (CCD). The surface morphologies of the newly synthesized nanocomposite membranes were analysed using Field Emission Scanning Electron Microscope (FESEM), functional groups using Fourier Transform Infrared Spectroscopy (FTIR), force measurement and imaging using Atomic force microscopy (AFM), and crystallinity using X-Ray Diffraction instrument (XRD). The findings from the screening suggested that the most influential factors that affect the permeability and selectivity are Pebax concentration and types of nanoadsorbent. The best condition was known to maximize the permeability and selectivity. The identified conditions were Pebax concentration at 5.5 wt% using 4.5 wt% nano-pineapple peel activated carbon and sonication time of 15 min which gave CO2 permeability, CO2/CH4 selectivity and CO2/N2 selectivity of 1537.08 Barrer, 40.21 and 41.39, respectively. The outcome of this study indicates that FFD was suitable to minimize and eliminate factors by considering the interaction among the factors involves in membrane film synthesis for excellent gas separation performance. Besides, the incorporation of this nanoadsorbents were reported to alter the polymer membrane structure and chemical properties which led to an improvement of the membrane’s performance that lie significantly near and above the Robeson upper bound limit, which satisfies both high selectivity as well as high permeability.